Siberian museums in the regional publishing landscape: traditions and new trends in the early XXI century - I. S. Troyak (Библиосфера)
The basic directions of museum publishing activity in Siberia in 2001-2015 are studied. Publications prepared by government and some private museums in the region are represented. Attention is paid to the introduction of new technologies in traditional forms of museum activity, which is implemented in particular through the production of e-publications or text placement on a museum site. It noted the lack of advertising of publications by Siberian museums that hinders their promotion to readers.